Eigen value approach to two dimensional problem in generalized magneto micropolar thermoelastic medium with rotation effect - R. Singh; V. Kumar (International Journal of Applied Mechanics and Engineering, 2016)
In this study an eigen value approach has been employed to examine the mechanical force applied along with a transverse magnetic field in a two dimensional generalized magneto micropolar thermoelastic infinite space. Results have been obtained by treating rotational velocity to be invariant. Integral transforms have been applied to solve the system of partial differential equations. Components of displacement, normal stress, tangential couple stress, temperature distribution, electric field and magnetic field have been obtained in the transformed domain. Finally numerical inversion technique has been used to invert the result in the physical domain. Graphical analysis has been done to described the study.